Alcohol-related morbidity and mortality following involuntary job loss - Marcus Eliason (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
The purpose of this study was to assess the association between involuntary job loss and alcohol-attributable morbidity and mortality. Swedish-linked employee-employer data were used to identify all establishment closures during 1990-1999, as well as the employees who were laid off and a comparison group. These data were merged with information on alcohol-attributable deaths and hospital admissions from the Causes of Death Register and the National Patient Register. The associations between job loss and alcohol-attributable morbidity and mortality during a follow-up period of 12 years were estimated by propensity score weighting methods. An excess risk of both alcohol-related hospitalization and mortality was found among both displaced men and women. For women, the wholly alcohol-attributable health problems were mainly limited to alcohol dependence, whereas men also had an increased risk of hospitalization from poisoning and alcohol-induced liver disease and pancreatitis. The findings support previous evidence of increased risks of alcohol-related morbidity/mortality following involuntary job loss, although the estimates presented herein are more conservative. In addition, the findings suggest that alcohol-related problems manifest differently in men and women.
Keywords: I10; I12; J63; J65; 330; alcohol; drinking; job loss; morbidity; mortality; plant closures